Digital marketing - Arif, Ali (Toronto Academic Press, 2024)
Digital marketing uses online platforms like email, social media, and mobile marketing to promote and sell products or services to potential customers. This text is an informative guide for anyone looking to expand their knowledge of online marketing. The book covers topics such as social media, email marketing, content marketing, SEO, and more. With practical advice and real-life case studies, readers can apply the strategies outlined in the book to their own digital marketing campaigns. Whether you're a beginner or an experienced marketer, this book offers insights and tips that can help you succeed in the digital space.